Evaluation of Self-Healing Performance of PE and PVA Concrete Using Flexural Test - Choonghyun Kang; Jungwon Huh; Quang Huy Tran; Kiseok Kwak (Advances in Materials Science and Engineering)
The self-healing performance of PE and PVA concrete was evaluated, by using the three-point bending test with a notch. Four different crack inducement days were applied (7, 28, 49, and 91 days), and the same 21 days of healing period were applied to each case. The self-healing environments were in 20°C water, and in the curing room with 20°C temperature and 60% humidity. The flexural strength and the initial flexural stiffness of before and after healing were compared. As a result, both the strength recovery effect and the stiffness recovery effect decreased with the delay of crack inducement, and specimens in the water environment showed higher healing effect than those in the air environment. PVA fiber showed a relatively greater recovery effect than PE fiber.